2022
DOI: 10.1038/s41417-022-00550-6
|View full text |Cite
|
Sign up to set email alerts
|

PDPN contributes to constructing immunosuppressive microenvironment in IDH wildtype glioma

Abstract: The tumor immunosuppressive microenvironment (IME) significantly affects tumor occurrence, progression, and prognosis, but the underlying molecular mechanisms remain to make known. We investigated the prognostic significance of PDPN and its role in IME in glioma. Weighted gene co-expression network analysis (WGCNA) found PDPN closely related to IDH wildtype status and higher immune score. Correlation analysis suggested PDPN was highly positively relevant to immune checkpoints expression and immune checkpoints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…29,30 Wang et al revealed the immunosuppressive microenvironment roles of Podoplanin (PDPN) in glioma with IDH wildtype. 31 Zhang et al successfully established a tryptophan metabolism-based model in glioma to predict these patients' prognosis and immune responses. 32 Liu et al showed that DNTTIP2 was significantly linked with macrophage infiltrations in…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 Wang et al revealed the immunosuppressive microenvironment roles of Podoplanin (PDPN) in glioma with IDH wildtype. 31 Zhang et al successfully established a tryptophan metabolism-based model in glioma to predict these patients' prognosis and immune responses. 32 Liu et al showed that DNTTIP2 was significantly linked with macrophage infiltrations in…”
Section: Discussionmentioning
confidence: 99%
“…Tumor microenvironment and immune cell infiltration have gradually been regarded as hotspots in glioma and they could be used to predict patents’ prognosis or immune responses 29,30 . Wang et al revealed the immunosuppressive microenvironment roles of Podoplanin (PDPN) in glioma with IDH wildtype 31 . Zhang et al successfully established a tryptophan metabolism‐based model in glioma to predict these patients’ prognosis and immune responses 32 .…”
Section: Discussionmentioning
confidence: 99%
“…IDH status also denote TME cell components differences between tumors with the wild-type isoform and those with the mutated IDH [ 48 ]. Unlike GBMs with IDH-wildtype, GBMs with the IDH mutation have been shown to have less M2 macrophage infiltration and fewer PD-1-expressing T cells [ 49 ]. A study based on samples from patients with GBM showed that there is less infiltration of TAMs in GBM with IDH mutation, being more proinflammatory, which could reflect a better prognosis for these patients, and the fact that microglia in mutated IDH also have a proinflammatory role [ 50 ].…”
Section: Tumor Microenvironment (Tme) In Gbm Nichesmentioning
confidence: 99%
“…PDPN‐positive cancer‐associated fibroblasts have been implicated with immune suppression in pancreatic adenocarcinoma and lung cancer 18,19 . In gliomas, PDPN expression is elevated in accordance with tumor malignancy 20 and correlated with radioresistance 21,22 . However, how PDPN regulates macrophage polarization in glioma remains unclear.…”
Section: Introductionmentioning
confidence: 99%